2005
DOI: 10.1051/0004-6361:20053513
|View full text |Cite
|
Sign up to set email alerts
|

Global characteristics of the first IBIS/ISGRI catalogue sources: unveiling a murky episode of binary star evolution

Abstract: INTEGRAL is the first gamma-ray astronomy mission with a sufficient sensitivity and angular resolution combination appropriate to the detection and identification of considerable numbers of gamma-ray emitting sources. The large field of view (∼30• zero response FWHM) enables INTEGRAL to survey the galactic plane on a regular (∼weekly) basis as part of the core programme. The first source catalogue, based on the 1st year of core programme data (∼5 Ms) has been completed and published (Bird et al. 2004, ApJ, 607… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 47 publications
6
37
2
Order By: Relevance
“…Using RXTE data, Grimm et al (2002) highlighted clear signatures of the spiral structure in the spatial distribution of HMXBs. In the same way, Dean et al (2005), Lutovinov et al (2005), Bodaghee et al (2007), and Bodaghee et al (2012) showed that HMXBs observed with INTEGRAL also seem to be associated with the spiral structure of the Galaxy. However, HMXB locations, mostly derived from their X-ray luminosity, are not well constrained and highly uncertain due to direct accretion occurring in HMXBs, well below the Eddington limit.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Using RXTE data, Grimm et al (2002) highlighted clear signatures of the spiral structure in the spatial distribution of HMXBs. In the same way, Dean et al (2005), Lutovinov et al (2005), Bodaghee et al (2007), and Bodaghee et al (2012) showed that HMXBs observed with INTEGRAL also seem to be associated with the spiral structure of the Galaxy. However, HMXB locations, mostly derived from their X-ray luminosity, are not well constrained and highly uncertain due to direct accretion occurring in HMXBs, well below the Eddington limit.…”
Section: Introductionmentioning
confidence: 65%
“…Indeed, since the spiral arm rotation velocity is different from the angular velocity of the stellar disk, we expect HMXB positions to be offset from the currently visible SFCs. This time lag was mentioned in Lutovinov et al (2005) and Dean et al (2005), but a deeper investigation of this issue was not possible due to the limited sample of HMXBs at that time. Shtykovskiy & Gilfanov (2007) evaluated the offset for the galaxy M51.…”
Section: Implication Of the Correlation On Hmxb Formation And Evolutionmentioning
confidence: 99%
“…As INTEGRAL observed the complete galactic plane and discovered many new high-mass X-ray binaries, several studies of their distribution were published Dean et al, 2005;Bodaghee et al, 2007Bodaghee et al, , 2012c. The distributions of HMXBs and LMXBs along the Galactic plane are shown in Fig.…”
Section: Distribution Of Hmxbs and Its Correlation With The Spiral Stmentioning
confidence: 99%
“…These sources lie within a few degrees of the Galactic plane and show some evidence for clustering near Galactic spiral arms (Lutovinov et al 2005a). Their X-ray fluxes are typically $1-10 millicrab in the hard X-ray band (Dean et al 2005), and their luminosities are mostly unknown due to large uncertainties on their distances, but they may have luminosities of 10 33 -10 36 ergs s À1 if they are at typical 1-10 kpc Galactic distances.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of IGR sources and HMXB evolution (Dean et al 2005), the very high column density IGR sources may be in an evolutionary stage during which the neutron star is spiraling toward its companion, becoming embedded in the wind from the high-mass companion. In this picture, we may be seeing IGR J16207À5129 early in this evolutionary phase, so that the neutron star is still in a low-density portion of the wind.…”
mentioning
confidence: 99%